Butterworth Pattern-based Simultaneous Damping and Tracking Controller Designs for Nanopositioning Systems - Russell, Douglas; San-Millan, Andres; Feliu, Vicente; Aphale, Sumeet S. (Frontiers in Mechanical Engineering, 2016)
The Butterworth filter is known to have maximally flat response. Incidentally, the same response is desired in precise positioning systems. This paper presents a method for obtaining a closed-loop Butterworth filter pattern using common control schemes for positioning applications, i.e. Integral Resonant Control (IRC), Integral Force Feedback (IFF), Positive Position Feedback (PPF), and Positive Velocity and Position Feedback (PVPF). Simulations show a significant increase in bandwidth over traditional design methods and verify the desired pole placement is achieved. The simulations also show a significant limitation of the achievable bandwidth in the case of IRC, IFF, and PPF. For this reason, only PVPF is considered in experimental analysis. Experiments are performed using a two-axis serial kinematic nanopositioning stage. The results show a significant improvement in bandwidth and increased positioning accuracy, specifically at the turn-around point. This allows a greater portion of the scan to be used and improved positioning accuracy at high scanning speeds.